Revision of fossil Metretopodidae (Insecta: Ephemeroptera) in Baltic amber—Part 3: Description of two new species of Siphloplecton Clemens, 1915, with notes on the re-discovered lectotype of Siphloplecton macrops (Pictet-Baraban & Hagen, 1856) - Staniczek, Arnold H.; Godunko, Roman J. (Zootaxa, 2016)
In this contribution, we provide a complementary description of the re-discovered lectotype of Siphloplecton macrops (Pictet-Baraban & Hagen, 1856). Additionally, complementary descriptions of S. barabani Staniczek & Godunko, 2012 and S. picteti Staniczek & Godunko, 2012 based on new material are given. Two new species, S. sartorii sp. nov. and S. gattolliati sp. nov., are described from male imagines and attributed to two newly defined species groups within Siphloplecton.